1990
DOI: 10.1111/j.2044-8279.1990.tb00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Outcomes of Truancy

Abstract: This paper presents some findings of a study into early adult outcomes of truancy, which was based on the National Child Development Study, a longitudinal survey of all people in Great Britain born in the week 3rd-9th March 1958. It was found that truancy is associated with lower status occupations, less stable career patterns and more unemployment. Among those who were working, former truants' incomes were not lower, but they were considerably less well off once their family situation was taken into account. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 1 publication
3
33
0
3
Order By: Relevance
“…Die ersten drei Gründe betreffen die Folgen des Schulschwänzens, die anderen einen möglichen Handlungs-und Interventionsbedarf: 1. Häufige Schulschwänzer erreichen oft keinen oder nur einen niedrigen Schulabschluss und sind daher lebenslang sozial und ökonomisch benachteiligt (Farrington 1980;Hibbett et al 1990;Furgusson et al 1995). 2.…”
Section: Problemunclassified
See 1 more Smart Citation
“…Die ersten drei Gründe betreffen die Folgen des Schulschwänzens, die anderen einen möglichen Handlungs-und Interventionsbedarf: 1. Häufige Schulschwänzer erreichen oft keinen oder nur einen niedrigen Schulabschluss und sind daher lebenslang sozial und ökonomisch benachteiligt (Farrington 1980;Hibbett et al 1990;Furgusson et al 1995). 2.…”
Section: Problemunclassified
“…Auch der oftmals nachgewiesene Zusammenhang zwischen Schulverweigerung und anderen Formen abweichenden Verhaltens (z.B. Glueck und Glueck 1950;Ball und Connolly 2000;Burgess et al 2002) sowie die Bedeutung der Schulverweigerung als Risikofaktor einer dauerhaften kriminellen Karriere (Hibbett et al 1990;Furgusson et al 1995) verweisen auf die Wirksamkeit der allgemeinen Orientierung an konventionellen Werten und Normen. 4 H6: Je stärker konventionelle Normen und Werte internalisiert sind, desto geringer das Ausmaß der Schulverweigerung.…”
Section: Theorien Und Hypothesenunclassified
“…Excessive school absenteeism and impaired peer relationships associated with anxiety also lead to poor vocational adjustment (Hibbert et al, 1990) and selfconcept problems (Asher & Coie, 1990), as well as psychiatric disorders later in life (Kovacs & Devlin, 1998). In addition, anxious children do not necessarily grow out of their discomfort (Kendall & Ollendick, 2004;Pine et al, 1998) with many becoming anxiety-disordered adults (Ollendick & King, 1994).…”
Section: Consequences Of Anxietymentioning
confidence: 99%
“…Research has shown that young people experiencing anxiety disorders have lower academic achievement (Ialongo, Edelsohn, Werthamer-Larsson, Crockett, & Kellam, 1995), peer relationship problems (Strauss, Frame, & Forehand, 1987) and impairments in general social competence (Messer & Beidel, 1994). Excessive school absenteeism and impaired peer relationships associated with anxiety lead to poor vocational adjustments (Hibbert, Fogelman, & Manor, 1990) and self-concept problems (Asher & Coie, 1990) as well as psychiatric disorders later in life (Kovacs & Devlin, 1998). Depression also affects young people in similar ways.…”
mentioning
confidence: 99%